Social Work and Social Services in Europe - a changing landscape - Lawrence, Susan; Lyons, Karen (Cuadernos de Trabajo Social, 2013)
This article considers some of the variations and similarities, as well as possible areas of convergence, in social welfare policies; the organisation of social services; the concerns; and the education and training of social professionals across Europe. It focuses particularly on the European Union as a political bloc within a wider Europe, and identifies some aspects of its role in shaping national policies and practices, including in the fields of migration and higher education. It presumes that global and regional trends and influences, together with international population mobility, indicate that social professionals may find themselves increasingly drawn into «trans-national» interventions and that they therefore need to be aware of welfare systems and professional policies and practices beyond national borders. Respect for cultural diversity and commitment to the promotion of human rights and social justice, nationally and internationally, are regarded as essential values to be shared by social professionals across Europe, as espoused by regional bodies representing social professionals and educators.